Review on practice and challenges of ICT integration as pedagogical tools in Ethiopian primary school curriculum implementation - Merga Hunde Gonfa; Asnake Lealem Birhanu; Kemal Mohammed Gendo (Springer, 2024)
Abstract These days' students are more comfortable with technology. Therefore, we need to start using technology in creative ways to make it less boring. The use of ICT in teaching has the potential to transform higher education. It's a dynamic approach to education. When compared to the conventional chalk and talk learning method, it offers additional advantages. For students, the entire educational process can occasionally seem tiresome. ICT use in the classroom is crucial in this digital age to provide students with the opportunity to acquire and apply the necessary 21st-century skills. Therefore, understanding the problems and difficulties associated with ICT use in education will help instructors get past these difficulties and become proficient users of technology. Since the introduction of information and communications technologies (ICT) into the classroom, educators have developed their perspectives about ICT's usefulness as a teaching tool, its impact on students' learning outcomes, and its influence on their self-assurance and competency. There are obstacles to ICT integration in education. Lack of time, resources, access, and technological help are some of the external obstacles that teachers must overcome.